PELAKSANAAN PEMBELAJARAN MENULIS CERITA FANTASI PADA SISWA KELAS VII SMP NEGERI 2 KOTA BENGKULU - Sandy, A’isyah Mutia; Purwadi, Agus Joko; Arono (Jurnal Korpus, 2022)
The purpose of this study was to determine how the implementation of learning to write fantasy story texts was carried out. The method used in this study was a descriptive method with a qualitative approach. The population in this study were students of class VII G and class VIII H students of SMP N 2 Bengkulu City. The data collection techniques used observation and documentation techniques. The data analysis technique used in this study was to use qualitative data analysis. data, presentation of data and drawing conclusions. The results showed that the implementation of learning was carried out in two meetings with an allocation of 45 minutes, where in the first meeting the students observed a fantasy story text and the second meeting the students watched a fantasy story video. The implementation of learning is carried out in three stages of learning, namely preliminary activities, namely attracting the attention of students by greeting and greeting students, teachers checking student attendance, raising students' learning motivation, asking questions related to the material, which core activities are in the implementation of learning. writing fantasy story texts using a scientific approach which has several stages, namely observing fantasy story texts, collecting information from what is observed, processing information based on tasks given by the teacher and conclusions carried out by Indonesian language teachers and class VII students of SMP N 2 Bengkulu City, and activities Closing is done only by saying greetings due to time constraints. At the end of the lesson the teacher gives an assessment of the learning outcomes based on the assessment criteria contained in the lesson plan made by the teacher.